Transformasi Representasi Perempuan Dalam Puisi Arab Modern: Kajian Historis Dan Estetika Sastra - Rabiatul Adawiyah Madawat M (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
This study examines the evolution of women's representation in modern Arabic poetry through a historical-diachronic approach. The research traces how Arabic poetry has undergone significant shifts in depicting women, from the neo-classical period through the contemporary era. Findings indicate that this thematic evolution reflects not only aesthetic developments in literary form, but also constitutes a broader cultural response to patriarchal structures embedded in Arab society. Pioneering figures such as Nizār Qabbānī played a central role in reimagining women as active subjects rather than passive objects. The study also identifies both internal drivers—such as growing social consciousness—and external influences, particularly Western literary movements, as catalysts for new perspectives on women in Arabic verse. The article concludes that modern Arabic poetry about women represents a multifaceted discourse encompassing identity formation, resistance to traditional conventions, and the humanization of women within a patriarchal social context.